Case report: Clinical and virological characteristics of aseptic meningitis caused by a recombinant echovirus 18 in an immunocompetent adult - Jiang, Chunmei; Xu, Zhixiang; Li, Jin; Zhang, Jiaqi; Xue, Xingkui; Jiang, Jingxia; Jiang, Guihua; Wang, Xisheng; Peng, Yun; Chen, Tian; Liu, Zhenzhen; Xie, Liu; et al. (Frontiers in Medicine, 2023)
Echovirus 18 has been recognized as an important causative pathogens of aseptic meningitis in young children around the world, and echovirus 18 induced meningitis was rarely found in immunocompetent adults. Here, we report the clinical and virological characteristics of aseptic meningitis caused by a recombinant echovirus 18 in an immunocompetent adult. A 31-year-old immunocompetent woman admitted to our hospital with fever, dizzy, severe headache, nausea and vomiting for one day and diagnosed as viral meningitis based on clinical manifestation and laboratory results from cerebrospinal fluid (CSF). The patient received antiviral treatment with ribavirin and interferon as soon as the enterovirus infection was identified using qRT-PCR and cured after 4 days. Two echovirus 18 strains were isolated from the oropharyngeal swab and CSF samples with single nucleotide difference located at 5’-UTR. Phylogenetic analyses based on the VP1 gene showed the two strains belonged to the subgenotype C2 and clustered with sequences obtained from China after 2015, while results from 3D polymerase region showed the two strains were closely related to the E30 strains. Bootscanning results using the 5’UTR to 2A regions and 2B to 3’UTR regions showed potential intertypic recombination had occurred in the 2B gene. Recombination analyses further confirmed that the two strains (echovirus 18) presented genome recombination with echovirus 30 in the nucleotide regions of 2B gene. To our knowledge, this is the first report of echovirus 18 induced meningitis in an immunocompetent adult from mainland China, highlighting the need for close surveillance of echovirus 18 both in children and adults in the future.